Creating counter-publics against the Italian mafia - Cayli, Baris (Javnost (Ljubljana), 2013)
This study aims to develop insight into the new media's struggle against the Mafia in Italy using the Libera Informazione, an anti-Mafia civil society organisation established in 2007, as a case study. The article argues that the endeavours of the Libera Informazione are aimed at creating a public spherefor anti-Mafia entries in the media and subsequently renewing public culture through channels in the constructed public sphere. During this process, communication strategies aim to inform the public at the local and national levels to increase consciousness about the political-criminal nexus and activities of the Mafia groups. Drawing on anthropological, moral, and reformist models of journalism, the author asserts that such a struggle is attainable in the long run, as it requires a consistent effort and inspiration, which already exist in the struggle of anti-Mafia media establishments against the Mafia in Italy.
Keywords: Italija; Italy; organizirani kriminal; mafija; javno mnenje; javna sfera; mass media; množični mediji